Social commerce Open Innovation in healthcare management: an exploration from a novel technology transfer approach. (19th May 2019) - Davies, Gareth Huw; Roderick, Sian; Huxtable-Thomas, Louisa
Abstract: This paper presents an Open Innovation approach, AgorIP, for commercialisation of opportunities within Health & Social Care and Life Sciences, piloted in south-west Wales. This approach, supported by Welsh Government, NHS Wales, universities and private sector aims to develop new markets and innovations, where all opportunities are rigorously assessed for existing and/or new market potential. In parallel, the empowerment of citizens to manage their personal and collective health, and to access information and services has become an important driver, becoming a disruptive development within the state-centric integrated health economy. This paper examines the relevant policy context and emerging portfolio of innovations within AgorIP to explore emergence of social commerce innovation in Health care management. Findings reflect the above dynamics and constraints, with innovations showing segmentation across geographic, demographic and disease-sufferer groups. The authors therefore offer the AgorIP initiative as an interesting space to observe the potential for Open Innovation of social commerce within the health sector.